2022
DOI: 10.3390/membranes12050510
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of ETFE Membrane and PTFE Membrane by Atmospheric DBD Plasma

Abstract: Fluorine resin membranes with excellent chemical resistance have great potential for the application of high-performance chemical protective clothing. However, it is difficult to integrate fluorine resins into other materials such as fabrics due to their lower surface energy and poor bondability, making the fabrication of composite fabrics and the further seal splicing challenging. In this study, atmospheric pressure dielectric barrier discharge (DBD) plasma in helium (He) and helium/acrylic acid (He/AA) mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…These changes can be attributed to the introduction of hydrophilic functional groups like C-O-C and -OH onto the PTFE surface. The key takeaway is that a relatively short N 2 plasma treatment (20 s) effectively alters the surface properties of both PFOA-and PFOL-coated PTFE, transforming them from highly hydrophobic (θ = 142 • ) to moderately hydrophilic (θ ≈ 80 • ) (comparable to He/AA plasma treatment showing 67.8 • for PTFE) [18]. This shift aligns with previous research [23] suggesting that N 2 plasma treatment can effectively render PTFE surfaces more water interactive.…”
Section: Apparent Contact Angle Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These changes can be attributed to the introduction of hydrophilic functional groups like C-O-C and -OH onto the PTFE surface. The key takeaway is that a relatively short N 2 plasma treatment (20 s) effectively alters the surface properties of both PFOA-and PFOL-coated PTFE, transforming them from highly hydrophobic (θ = 142 • ) to moderately hydrophilic (θ ≈ 80 • ) (comparable to He/AA plasma treatment showing 67.8 • for PTFE) [18]. This shift aligns with previous research [23] suggesting that N 2 plasma treatment can effectively render PTFE surfaces more water interactive.…”
Section: Apparent Contact Angle Analysismentioning
confidence: 99%
“…They found that the plasma treatment duration of 20 min is enough to create a chemically modified surface possessing a reduced contact angle of 43 • and an eight-fold increase in hydrogen evolution rate. Ji et al [18] modified the surface of two fluorine resin membranes, ethylene tetrafluoroethylene (ETFE) and polytetrafluoroethylene (PTFE) membranes, by means of atmospheric pressure dielectric barrier discharge (DBD) plasma. The He/AA (helium/acrylic acid) plasma treatment results in producing stable grafted polyacrylic acid (g-PAA) on the membrane surface and improved the polarity and adhesion strength of the fluoro-resin membranes with decreased water contact angle values from 95.83 • to 49.9 • for ETFE membrane and from 109.9 • to 67.8 • for PTFE membrane.…”
Section: Introductionmentioning
confidence: 99%
“…With the constant advancement of membrane separation technology, its applicability is rapidly growing. Membrane filtration technology is currently applicable in various industrial fields for serving various purposes such as in high performance chemical reactive clothing [ 8 ], laser ignition [ 9 ], and desalination of seawater [ 10 ]. Based on the techniques used to create a vapor pressure gradient across the membrane and collect the transported vapors from the permeate side, the MD processes are categorized into four basic configurations [ 7 ] which have crucial separation performance and operating costs [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods can readily damage PTFE structures and cause environmental pollution. As a dry treatment method, plasma treatment is widely used for the surface modification of PTFE, which can introduce a variety of active functional groups on the surface in a short time [ 28 , 29 , 30 , 31 , 32 , 33 ]. However, the wettability after plasma treatment depends on numerous process parameters, such as the type of discharge, feed gas, working pressure, input power, and treatment time.…”
Section: Introductionmentioning
confidence: 99%